2010
DOI: 10.1007/s00167-010-1249-3
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of revision TKA: a review of the literature

Abstract: Based on the current literature, no final statement can be drawn regarding the optimal fixation technique in revision TKA. Future RCTs are needed to enable conclusive statements about the possible advantages and disadvantages of the single fixation techniques, although the clinical implementation often is critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 41 publications
(92 reference statements)
0
32
0
1
Order By: Relevance
“…The best method of fixation of the tibial component and the best length of tibial stem in revision TKA are unclear. There have been studies advocating fully cemented tibial components with stems of variable length, uncemented long stem components, and hybrid fixation with a cemented tibial tray and uncemented long stem [3]. There are specific advantages and possible disadvantages with all three techniques; thus, a consensus has not been reached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best method of fixation of the tibial component and the best length of tibial stem in revision TKA are unclear. There have been studies advocating fully cemented tibial components with stems of variable length, uncemented long stem components, and hybrid fixation with a cemented tibial tray and uncemented long stem [3]. There are specific advantages and possible disadvantages with all three techniques; thus, a consensus has not been reached.…”
Section: Discussionmentioning
confidence: 99%
“…Fixation of the revision modular tibial component can be performed with cement, with cementless porous-coated components, or a hybrid technique with cement fixation of the proximal tibial tray but a press-fit of the distal stem. A recent systematic review of the literature evaluated the results of these three methods of fixation and stated that no final recommendation could be made regarding the optimal fixation technique in revision TKA [3]. However, patients who have revision with ''long'' press-fit cementless stems seem to have more tibial stem-tip pain and lower knee scores [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Stem size, offset adaptors, stress shielding and the presence of either cement or bony on-growth can also complicate further revision surgery. Beckmann et al 3 recently published a review of the literature on revision knee replacement fixation. It was indicated that the majority of recent research has dealt with the comparison of hybrid and cemented fixation, reporting comparable rates of loosening and clinical outcomes for both methods.…”
Section: Discussionmentioning
confidence: 99%
“…It was indicated that the majority of recent research has dealt with the comparison of hybrid and cemented fixation, reporting comparable rates of loosening and clinical outcomes for both methods. 3 Fewer studies were available for cementless fixation. Overall the authors of the review could not make a final statement recommending one form of fixation over the other, based on clinical outcome studies in the current literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation